Learning from Trading - Kandel, Shmuel; Ofer, Aharon R.; Sarig, Oded (Review of Financial Studies, 1993)
The incorporation of diverse information into asset prices is empirically examined in an actual securities market with multiple rounds of trade. Using prices of Israeli index and nominal bonds of equal maturity, we calculate implied expectations of inflation that has already occurred but for which the official statistic has not yet been announced. Learning is defined as the convergence of these expectations to the actual level of inflation in the period after the end of the month but before the announcement of the official statistic. We find that the variance of the inflation expectation errors decreases with trading days in this period. The decline in the variance suggests that investors learn, by repeatedly observing prices, about the distribution of other investors' information. We also find a positive relation between the dispersion of relative price changes and the size of the inflation‐expectation errors on the first round of trade. The correlation diminishes as investors learn about the distribution of inflation information in the economy.